Primary Frozen Shoulder Syndrome: Arthroscopic Capsular Release - Guillermo Arce, M.D. (Arthroscopy Techniques, 2015)
Idiopathic adhesive capsulitis, or primary frozen shoulder syndrome, is a fairly common orthopaedic problem characterized by shoulder pain and loss of motion. In most cases, conservative treatment (6-month physical therapy program and intra-articular steroid injections) improves symptoms and restores shoulder motion. In refractory cases, arthroscopic capsular release is indicated. This surgical procedure carries several advantages over other treatment modalities. First, it provides precise and controlled release of the capsule and ligaments, reducing the risk of traumatic complications observed after forceful shoulder manipulation. Second, release of the capsule and the involved structures with a radiofrequency device delays healing, which prevents adhesion formation. Third, the technique is straightforward, and an oral postoperative steroid program decreases pain and allows for a pleasant early rehabilitation program. Fourth, the procedure is performed with the patient fully awake under an interscalene block, which boosts the patient's confidence and adherence to the physical therapy protocol. In patients with refractory primary frozen shoulder syndrome, arthroscopic capsular release emerges as a suitable option that leads to a faster and long-lasting recovery.